Strategi Promosi Digital Brand MS GLOW Cabang Makassar di Sosial Media Instagram - Gosal, Gabrielle Valentine; Djalil, Nur Alim; Hadiati, Hadiati (IAI Nasional Laa Roiba Bogor, 2024)
This study aims to determine the digital promotion strategy of the MS GLOW brand, Makassar branch on social media Instagram qualitative research with a case study approach by taking the object of research is MS GLOW Makassar branch. To fulfil these objectives, a qualitative research was conducted at MS GLOW Makassar branch. Research data was collected through observation and in-depth interviews. The data findings were then analysed, in order to achieve the desired results. The results of this study are to determine the Digital Brand Promotion Strategy of MS GLOW Makassar branch. This promotion is carried out by utilising the 4P marketing mix (product, price, place, and promotion) to ensure a more targeted approach. In addition, they also market dowry and bridal products by utilising the various features available on the Instagram application. In this case, followers who do not give likes or comments on each upload, the appearance of negative feedback in the comments column.